Fatigue in Parkinson’s disease—A narrative review - Baikuntha Panigrahi; Kanchana S. Pillai; Divya M. Radhakrishnan; Roopa Rajan; Achal K. Srivastava (Annals of Movement Disorders)
Although fatigue is a common non-motor symptom of Parkinson’s disease (PD), it is often overlooked during routine assessments of individuals with PD. This can be attributed partly to the lack of recognition of this symptom and the coexistence of other confounding symptoms, such as apathy, somnolence, and depression. However, considering the effects of fatigue on the quality of life (QoL) of individuals with PD, it is crucial to review its causes and management strategies. According to the diagnostic criteria for PD-related fatigue, patients must report significantly reduced energy levels or an increased perception of effort disproportionate to their attempted activities. PD-related fatigue can be divided into central and peripheral types. Peripheral fatigue involves muscle weakness and impaired voluntary movements, influenced by tremors and bradykinesia. Central fatigue, which can be divided into mental and physical subtypes, manifests as persistent exhaustion without peripheral motor deficits. The pathophysiology of central fatigue in PD is complex. It involves dysfunction in the striato–limbic–serotonergic system, imbalance of neurotransmitters (dopamine and serotonin), as well as hypoconnectivity in the supplementary motor area and hyperconnectivity in the default mode network. Emerging evidence suggests that neuroinflammation and autonomic dysfunction may contribute to fatigue. Fatigue in PD is treated using pharmacological therapies (such as dopaminergic agents, antidepressants, methylphenidate, and modafinil) and non-pharmacological interventions (such as exercise). There is a gap in the current understanding, measurement, and treatment of fatigue in PD. A deeper understanding of the patho-mechanisms of fatigue in PD is needed to establish evidence-based treatment guidelines. The QoL of individuals with PD can be improved by focusing on person-centered interventions targeting fatigue.